2014
DOI: 10.3354/meps10916
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic variation in temperature drives performance of kelp gametophytes during warming

Abstract: The capacity for thermal adjustment or adaptation is critical to population persistence in a warming ocean. Understanding such performance across a species' range can give insights into the extent of possible adjustment as well as spatial variation in vulnerability. This study tested the effects of temperature on the density and size of gametophytes of the habitatforming kelp Ecklonia radiata, across its Australian distribution (between ~9° and ~33°S). Gametophytes from warm, intermediate and cool biogeographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 47 publications
5
55
0
Order By: Relevance
“…However, these effects were generally observed over temperature ranges that span 2°-20°C over ambient (Fain and Murray 1982, Deysher and Dean 1986, Wernberg et al 2010, Brown et al 2014. Kelp populations are known to be locally adapted to the conditions they typically experience, with populations displaying different responses to changes in temperature throughout a latitudinal range (Buschmann et al 2004, Mohring et al 2014. However, the mean temperatures observed in this study (11.9°-12.7°C) are well within the thermal range known for M. pyrifera (8-23°C;Schiel and Foster 2015).…”
Section: Discussionsupporting
confidence: 47%
“…However, these effects were generally observed over temperature ranges that span 2°-20°C over ambient (Fain and Murray 1982, Deysher and Dean 1986, Wernberg et al 2010, Brown et al 2014. Kelp populations are known to be locally adapted to the conditions they typically experience, with populations displaying different responses to changes in temperature throughout a latitudinal range (Buschmann et al 2004, Mohring et al 2014. However, the mean temperatures observed in this study (11.9°-12.7°C) are well within the thermal range known for M. pyrifera (8-23°C;Schiel and Foster 2015).…”
Section: Discussionsupporting
confidence: 47%
“…These assumptions do not take into account that local populations may have adapted to their respective conditions (e.g. Mohring et al 2014) and thus may show a different response to multifactorial changes than just one population. Furthermore the current investigation did not verify the situation in the field or consider spores taken throughout the season, but it clearly shows that responses of kelp life stages vary in time.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported both pronounced variability and little-to-no variability between populations. For example, Ecklonia radiata populations in Australia and New Zealand were found to have optimal performances reflective of those experienced by the environment in which they persist (Novaczek 1984, Mohring et al 2014 whereas no intraspecific variability in the gametophyte stage was reported for four kelp species in the northeast Atlantic (Bolton and Lüning 1982). Whether such differences will be important in the context of species redistributions will depend on the comparative vulnerability of the life stages.…”
Section: General Patternsmentioning
confidence: 98%